Pedagogic Competence for Early Childhood Educators as A Requirement for Merdeka Belajar: A Case Study in Banten Province - Tjut Dwi Anggraini Damcha; Hamid Patilima; Nuris Azizah; Satia Imelda Yuanita; Helmi; Ria Andriyani (International Conferences on Early Childhood Education Proceedings, 2023)
Teachers face challenges in teaching and learning in the industrial revolution era 4.0 and Society 5.0. Ensuring students have communication, collaboration, creation, and critical thinking competencies. This article aims to analyze the educational competence of early childhood educators in realizing Merdeka Belajar in Banten Province, Indonesia. Pedagogic competence is the ability needed by educators to carry out the program Sekolah Penggerak, Guru Penggerak, and Implementation of the Kurikulum Merdeka in their schools. These three programs are the pillars for achieving Merdeka Belajar. The research method used was to collect information through written interviews using the Google Form, which was distributed to representatives of the education and culture offices in 8 districts and cities in Banten Province, including the heads of the PNF and Kasi PAUD, in addition to PAUD supervisors and inspectors in 8 communities and towns. as well as representatives from various schools and early childhood education teachers throughout Banten Province. The results of this study indicate that the 106 informants who are educators and related education stakeholders already understand the Sekolah Penggerak, Guru Penggerak, and Merdeka Curriculum programs and have pedagogic competencies that can support the realization of Merdeka Belajar, but further observations are still needed regarding the implementation of these programs in schools.